Women in Leadership: A Critical Reading of Khnata Bint Bakkar’s Role in Moroccan History - Ahmed Lehfid; Ghali Lehfid; Abdelaaziz El Bakkali (International Journal of Qualitative Research, 2026)
The present article investigates the life, political contributions, and historical significance of Khnata Bint Bakkar, a prominent female figure in Moroccan history. The study addresses the problem of women’s historical underrepresentation in political narratives and examines how Khnata Bint Bakkar navigated and exercised agency within a male-dominated political sphere. Based on a qualitative research approach, the study employs content analysis of the documentary episode on Khnata Bint Bakkar from the series Ten Women from History (2M, Morocco) and corroborates the documentary’s accounts with secondary historical sources. The research objectives are to identify her political and diplomatic roles, assess her influence on decision-making and governance, and analyze her mentorship of successive rulers. Findings reveal that Khnata Bint Bakkar played multifaceted roles, namely advisor, diplomat, military manager, and mentor, all of which contributed to the consolidation and stability of the Moroccan kingdom during the reigns of Sultan Moulay Ismail, Sultan Moulay Abdellah, and Sultan Sidi Mohamed. Moreover, her later withdrawal from politics did not diminish her legacy, as she continued to impact society through humanitarian work and religious practice. The study highlights her strategic acumen and leadership, demonstrating the critical role of women in Moroccan political history. These findings have implications for historiography as they emphasize the importance of recognizing women’s agency and contributions in shaping political and social structures.